Health Accelerator and Financial Frictions in Macroeconomic Modelling - Firano Zakaria; Filali Adib Fatine (SAGE Open)
In this paper, we have developed a new approach to macroeconomic modelling by proposing to introduce the agent’s behaviour in a pandemic situation. In the form of health frictions that alter the economic agent’s behaviour in crisis situations, we have set up a DSGE model whose behavioural functions take into account the existence of healthy and infected populations. The novelty of this work is the inclusion of the two frictions; health and financial, the idea is to succeed in describing the macro-financial dynamics in a pandemic situation. The results obtained confirm the existence of a health accelerator that amplifies macroeconomic shocks. JEL classification: G21, G28, E42, E32